Silencing Sexually Transmitted Infections: Topical siRNA-Based Interventions for the Prevention of HIV and HSV. (12th January 2014) - Wheeler, Lee Adam
Abstract : The global impact of sexually transmitted infections (STIs) is significant. The sexual transmission of viruses such as herpes simplex virus type-2 (HSV-2) and the human immunodeficiency virus type-1 (HIV-1), has been especially difficult to control. To date, no effective vaccines have been developed to prevent the transmission of these STIs. Although antiretroviral drugs have been remarkably successful in treating the symptoms associated with these viral infections, the feasibility of their widespread use for prevention purposes may be more limited. Microbicides might provide an attractive alternative option to reduce their spread. In particular, topically applied small inhibitory RNAs (siRNAs) have been shown to not only block transmission of viral STIs to mucosal tissues both in vitro and in vivo, but also confer durable knockdown of target gene expression, thereby circumventing the need to apply a microbicide around the time of sexual encounter, when compliance is mostly difficult. Despite numerous clinical trials currently testing the efficacy of siRNA-based therapeutics, they have yet to be approved for use in the treatment of viral STIs. While several obstacles to their successful implementation in the clinic still exist, promising preclinical studies suggest that siRNAs are a viable modality for the future prevention and treatment of HSV and HIV.